2015
DOI: 10.1002/mabi.201400504
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Responses of Cancer Cells on Nanoscaffolds for Adhesion Size Control

Abstract: A mechano-reciprocal interaction plays a critical role for cancer cells searching for favorable metastasis sites. For this study, we utilized nanoscaffolds that can control the maturation of focal adhesions in order to investigate how cancer cells mechanically respond to their nanoenvironments. We found that prostate cancer cells showed linearly decreasing proliferation rate and mechanical stiffness as the size of nanoislands on nanoscaffolds where the cells were grown decreases. This mechanical signature was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Furthermore, AFM has been used for investigating the mechanical response of cancer cells on different substrates. Park et al studied prostate and breast cancer cells that were cultured on nanoscafolds and showed that different cancer cell lines have distinct response to substrate characteristics such as size and nanomechanical properties [175]. Additionally, AFM can be used for studying cell-cell interaction.…”
Section: Afm and Specific Pathological Conditionsmentioning
confidence: 99%
“…Furthermore, AFM has been used for investigating the mechanical response of cancer cells on different substrates. Park et al studied prostate and breast cancer cells that were cultured on nanoscafolds and showed that different cancer cell lines have distinct response to substrate characteristics such as size and nanomechanical properties [175]. Additionally, AFM can be used for studying cell-cell interaction.…”
Section: Afm and Specific Pathological Conditionsmentioning
confidence: 99%
“…cell manipulations with atomic force microscope and optical tweezer techniques). 34,35 In addition to these approaches, the substrates were developed to measure traction forces exerted by the cells. Microbeads embedded elastic substrates have been used to measure the force exerted by the cells to the substrates, which is called traction force microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques include optical stretcher [102][103][104][105], micropipette aspiration [106], microfluidics [107], magnetic tweezers [108][109][110], and AFM [111][112][113][114]. Among these, AFM has been the most widely utilized in bio-mechanical assays [13,52,[115][116][117][118].…”
Section: Mechanical Compliancementioning
confidence: 99%